Community-based Cardiac Rehabilitation Improved Adherence to Medication, Quality of Life and Rehospitalization Among Stable Coronary Artery Patients: A Cohort Study - Muchammad Dzikrul Haq Karimullah; Mohammad Saifur Rohman; Tonny Adriyanto; Cholid Tri Tjahjono; Sasmojo Widito (Heart Science Journal, 2020)
Background : Community-based cardiac rehabilitation interventions have been known as an important aspect of secondary prevention. However, no data are available regarding the benefit of this program in Indonesian coronary artery disease (CAD) patients treated with optimal medication.Objectives : To assess the benefit of community-based cardiac rehabilitation on patient adherence to the drugs, quality of life (QoL) and MACE, in stable CAD.Methods : An observational prospective cohort study recruited the Malang community of cardiovascular care (MC3) members as an intervention group and Aisyah Islamic hospital patients in Malang, Indonesia, as a control, for a year follow up. Member of MC3 has regular aerobic exercise, education regarding the disease, the importance of the drugs, and its side effect in addition to standard education given in outpatient clinic setting as the control group members. A validated MMS-8, QOL (SF-36), and SAQ questionnaire were used to assess adherence to the drugs, QoL, and MACE of participants.Results: A total of 73 interventions and 73 control patients were enrolled for the study. Our findings showed that intervention patients were 2.04-fold associated with having a better physical function and 3.85-fold better compliance than control patients. The hospitalization rate also significantly lower in members of the intervention group (MC3). However, no significant difference observed among the two groups. Moreover, in the subgroup analysis, it shows that the intervention group who had participated for 2 years had the highest value of MMS-8 compared to the other groups with p < 0.005.Conclusion: Our study reveals that community based cardiac rehabilitation intervention have better adherence to medication and quality of life than patients control, and also could reduce rehospitalization in stable CAD patients.